Malondialdehyde (MDA) Concentration and Histopathological Image of Indomethacine-Induced Wistar Rat,Rattus norvegicus,With Inflammatory Bowel Disease (IBD) After Mas Ngur Oyster (Atactodea striata) Extract Therapy - Celcius Waranmaselembun; Agustiana Agustiana; Firlianty Firlianty; Yuliana Anastasia Ngamel; Silvester B. Pratasik (Eduvest - Journal of Universal Studies, 2023)
Inflammatory Bowel Disease (IBD) is an inflammatory disease occurring in gastirct tract, particularly colon, that could result from the side effect of anti-inflammatory non-steroid(AINS) drug utilization, such asindomethacine. Mas ngur oysters (Atactodea striata) have long been known by people of Kei-Southeast Mallucas as traditional medicine, but its use in reducing MDA level in rat with IBD has not been studied. This study was aimed at measuring the ability of the bioactive compounds contained in mas ngur oyster powder extract to reduce the MDA level in the ileum of indomethacine-induced rat with IBD and providing the histological image of the ileum after therapized with mas ngur oyster extract. Test animals were 8-12 week old-male rats (Rattus norvegicus) of 150 - 200 g BW. They were separated into 3 groups,healthy, sick (induced with 15 mg/kg BW indomethacine), therapy goups (15 mg/kg BW indomethacine oral induction then treated with mas ngur oyster powder of100, 400, 700 mg/kg BW). Indomethacine induction of 15 mg/kg BWand therapy of mas ngur oyster powder extract were administered orally. MDA level was measured usingThiobarbituric Acid (TBA)test and histological image of the ileum using Hematoxylin-Eosin staining. Results showed that mas ngur extract therapy gave significant effectin MDA level (P<0.05) and difference between the treatments with effective dose of400 mg/kg BW